Observations of debris flows at chalk cliffs, colorado, usa: part 2, changes in surface morphometry from terrestrial laser scanning in the summer of 2009 - Staley, Dennis M.; Wasklewicz, Thad A.; Coe, Jeffrey A.; Kean, Jason W.; McCoy, Scott W.; Tucker, Greg E. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"High resolution topographic data that quantify changes in channel form caused by sequential debris flows in natural channels are rare at the reach scale. Terrestrial laser scanning (TLS) techniques are utilized to capture morphological changes brought about by a high-frequency of debris-flow events at Chalk Cliffs, Colorado. The purpose of this paper is to compare and contrast the topographic response of a natural channel to the documented debris-flow events. TLS survey data allowed for the generation of high-resolution (2-cm) digital terrain models (DTM) of the channel. A robust network of twelve permanent control points permitted repeat scanning sessions that provided multiple DTM to evaluate fine-scale topographic change associated with three debris-flow events. Difference surfaces from the DTM permit the interpretations of spatial variations in channel morphometry and net volume of material deposited and eroded within and between a series of channel reaches. Each channel reach experienced erosion, deposition, and both net volumetric gains and losses were measured. Analysis of potential relationships between erosion and deposition magnitudes yielded no strong correlations with measures of channel-reach morphometry, suggesting that channel reach-specific predictions of potential erosion or deposition locations or rates cannot be adequately derived from statistical analyses of pre-event channel-reach morphometry."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">High resolution topographic data that quantify changes in channel form caused by sequential debris flows in natural channels are rare at the reach scale. Terrestrial laser scanning (TLS) techniques are utilized to capture morphological changes brought about by a high-frequency of debris-flow events at Chalk Cliffs, Colorado. The purpose of this paper is to compare and contrast the topographic response of a natural channel to the documented debris-flow events. TLS survey data allowed for the generation of high-resolution (2-cm) digital terrain models (DTM) of the channel. A robust network of twelve permanent control points permitted repeat scanning sessions that provided multiple DTM to evaluate fine-scale topographic change associated with three debris-flow events. Difference surfaces from the DTM permit the interpretations of spatial variations in channel morphometry and net volume of material deposited and eroded within and between a series of channel reaches. Each channel reach experienced erosion, deposition, and both net volumetric gains and losses were measured. Analysis of potential relationships between erosion and deposition magnitudes yielded no strong correlations with measures of channel-reach morphometry, suggesting that channel reach-specific predictions of potential erosion or deposition locations or rates cannot be adequately derived from statistical analyses of pre-event channel-reach morphometry.